Novinarsko sporočanje o poskusnem izračunu vrednosti nepremičnin v Sloveniji - Erjavec, Karmen (Geodetski vestnik, 2011)
By researching news reporting on the test calculation of real estate value in Slovenia, this study fills a gap in researching media images of the work and community of geodesy. A quantitative content analysis and a critical discourse analysis of news items on this project in five Slovenian daily newspapers reveal a predominantly negative view of its success, as almost 60% of news items described it negatively, while a positive view was found only in nearly 12% of reports. An analysis of topics also shows that newspapers emphasized the negative aspects of the project above all. An analysis of sources confirms the key role of official sources, particularly the Surveying and Mapping Authority of the Republic Slovenia (GURS). "Ordinary citizens" were unexpectedly used as a source relatively frequently. The qualitative analysis enabled a precise insight into the prevalent macro-proposition about owners' discontent with the work of GURS and into the much less frequently included macro-propositions about GURS performing its work well, and about its carrying out an extensive, important project. An analysis of the words used reveals how journalists, by using words with extremely negative connotations and emotional descriptions of readers' experiences, constructed a meaning that diminishes the reputation of GURS and the geodesic community. The results raise doubts about whether the citizens were well informed about the project. A question also appears about whether the strategy of the geodesic community's communication with the media has been planned and performed well enough.
Keywords: Journalism; Mass media; Množični mediji; Nepremičnine; Novinarstvo; Poročanje; Real estate; Reporting; Slovenia; Slovenija